Prophets, pastors and profiteering: exploring external providers' enactment of pastoral power in school wellbeing programs. Issue 2 (3rd March 2020) - McCuaig, Louise; Woolcock, Liz; Stylianou, Michalis; Ng, Johan Y.Y.; Ha, Amy S.
ABSTRACT: This paper explores the governance practices that external providers of school wellbeing programs employ in their contribution to the subjectification function of education. In neoliberal times where this 'game' of subjectification has become more open, governmentality scholars have been challenged to provide more robust insight into how discourses permeate individual subjectivities. In response, we draw on recent theorising of Foucault's pastoral power concept and a resulting analytic framework of four interlinked practices to explore external providers' endeavours to 'shepherd' students, teachers and parents in the practices and responsibilities of personal wellbeing. Our data revealed that discourse tension and conflict emerges within school communities' increasingly 'messy' pastoral terrain. In conclusion, we suggest that more empirical and theoretical insight into actors' resistance and agency within the pastoral power landscape of schools offers a vital contribution to our understanding of external providers' influence on education policy and enactment.